KEABSAHAN PERALIHAN HAK ATAS TANAH MELALUI JUAL BELI DI BAWAH TANGAN MENURUT HUKUM PERTANAHAN (STUDI KASUS PUTUSAN PENGADILAN NEGERI TANGERANG NOMOR: 376/PDT.G/2017/PN.TNG) - Michelle Velisia; Hanafi Tanawijaya (Jurnal Hukum Adigama, 2021)
Land is one of the basic human needs and limited land can cause problems because it will encourage the purchase and sale of land and the process of land right switchover. The purchase and sale agreement is law that was born as a result of community needs. This research was conducted because there was one of decision that contained an incident that there hand been a sale and purchase of land in 1999 but used a receipt, the buyer hasn't has not transferred the name of the certificate and the seller's whereabouts are not found before the legalization of the sale and purchase is carried out so that the buyer files a lawsuit to the court and the buyer/plaintiff's request is granted because the seller/defendant did not come during the trial and did not send a guardian to come to the trial. How is the validity of the sale and purchase that is carried out using only proof of receipt without an authentic deed? The research method used by the author is a normative legal research method that is library research, examines the decision of the District Court Number 376/PDT.G/2017/PN.TNG and is associated with statutory regulations, case approaches, and conceptual approaches. Sources of data used in this study are primary and secondary data sources using data collection techniques used, namely interviews and literature study. Based on the research data, it is known that the legitimacy of buying and selling land rights under the hands that have not been carried out before the PPAT does not automatically become illegal according to law and shows that there are still people who have not legally bought and sold according to the law it is detrimental to the buyer that the sale and purchase of land should use an authentic deed because if it does not have an authentic deed, it cannot be renamed the certificate.